GAMBARAN SISTEM PENGELOLAAN SAMPAH RUMAH TANGGA DI DAERAH PESISIR KELURAHAN SENGGARANG, KOTA TANJUNGPINANG - Diansafitri, Mutia; Putri, Merlina; Pitriyanti, Luh (Poltekkes Kemenkes Bengkulu, 2022)
Senggarang Village RT 002 is part of the Tanjungpinang Kota sub-district, most of the population lives on the coast, after observing it you can see trash scattered in the sea. The research objective was to describe the household waste management system in Senggarang Village RT 002. This type of research used a descriptive method with a total sampling technique of 51 families. How to collect data with questionnaires and interviews. Data collection was carried out in December 2021 - April 2022. The results of household waste segregation that met the requirements was 20 KK (39.2%). The results of the research on waste collection showed was 30 KK (58.8%) met the requirements. The results of research on household waste transportation, processing and infrastructure showed was 51 KK (100%) did not meet the requirements. The conclusion of this study is that household waste management in Senggarang Village RT 002 does not meet the requirements. Advice for the local government so that household waste processing meets the requirements can be by holding counseling on household waste management, providing Temporary Shelters (TPS), providing garbage collectors, and facilities such as garbage trucks and carts, and the community is expected to care about the environment.